Meat Broiler Supply Chain Analysis at Malang City, East Java (A Study on One Meat Broiler Distributor) - Nugroho , Bambang Ali; Winarto, Priyo Sugeng (International Journal of Poultry Science, 2011)
The research has been conducted on April 1st to May 1st 2010, at Malang City, East Java Province. Result of research shows four patterns of marketing chain. The first marketing chain is farmer/producer → wholesaler → retailer → consumer. The second marketing chain is farmer/producer & wholesaler → RPA → retailer → consumer. The third marketing chain is farmer/producer → wholesaler → restaurant → consumer. The final marketing chain is farmer/producer → wholesaler → retailer → broker → consumer. Basically, value chain on each chain is about the unbalanced profit share taken on each chain, the final marketing agent is inclined to take the highest profit, thus make the price on consumers become higher. The result of marketing margin analysis indicates that the margin distribution of first chain is 26.52%, while those of second, third and fourth chain are 28.08%, 13.36% and 32.04%. Farmer’s share in first chain is 44.72%, while those in second, third and fourth chain are 43.57%, 61.56% and 40.22%. Profit share per cost of each farmer is similar in rate of 0.08. The profit share of broker in the first chain is 0.47, while those in second, third and fourth chain are 0.49, 0.09 and 0.59.